The “Self” in Work Organizations: A Conceptual Review - Brief, Arthur P.; Aldag, Ramon J. (Academy of Management Review, 1981)
Currently popular models of employee behavior generally grant the individual a relatively passive role. It has recently been argued that a more comprehensive view would recognize three-way reciprocal interaction among employee behaviors, cognitions, and the environment. This paper contributes to this expanded viewpoint, focusing specifically on the role of the self and including characteristics and consequences of self-reinforcement systems, self-efficacy expectations, and an integrative model of the self in organizational research. This relatively broad viewpoint has potentially important implications for organizational behavior.